'Would it sell more pork?' Pig farmers' perceptions of Real Welfare, the welfare outcome component of their farm assurance scheme. (20th May 2019) - Hockenhull, J.; Main, D. C. J.; Mullan, S.
Abstract : In the UK, the pig industry is leading the way in the adoption of welfare outcome measures as part of their farm assurance scheme. The welfare outcome assessment (WOA ), known as Real Welfare, is conducted by the farmers' own veterinary surgeon. For the first time, this has allowed the pig industry to evaluate welfare by directly assessing the animal itself and to document the welfare of the UK pig industry as a whole. Farmer perspectives of the addition of a welfare outcome assessment to their farm assurance scheme have yet to be explored. Here, we investigate how the introduction of the Real Welfare protocol has been perceived by the farmers involved, what value it has (if any), whether any practical changes on farm have been a direct consequence of Real Welfare and ultimately whether they consider that the welfare of their pigs has been improved by the introduction of the Real Welfare protocol. Semi-structured interviews with 15 English pig farmers were conducted to explore their perceptions and experiences of the Real Welfare process. Our findings fall into three key areas: the lived experience of Real Welfare, on-farm changes resulting from Real Welfare and suggested improvements to the Real Welfare process as it currently stands. In all the three areas, the value farmers placed on the addition of WOA appeared to reflect their veterinary surgeon's attitude towards the Real Welfare protocol. If the vet was engaged in the process and actively included the farmer, for example through discussion of their findings, the farmers interviewed had a greater appreciation of the benefits of Real Welfare themselves. It is recommended that future similar schemes should work with veterinary surgeons to ensure their understanding and engagement with the process, as well as identifying and promoting how the scheme will practically benefit individual farmers rather than assuming that they will be motivated to engage for the good of the industry alone. Retailers should be encouraged to use Real Welfare as a marketing tool for pig products to enhance the perceived commercial value of this protocol to farmers.